تأثير مسحوق أوراق نبات اليوكالبتوس في نمو Erwinia carotovora subsp.Carotovora واستعماله للسيطرة على مرض التعفن الطري في البطاطا - الكبيسي, سناء سعود (Al-Nahrain Journal of Science, 2018)
Isolate causes soft rot disease was taken from potato tubers which were incubated in laboratory under artificial conditions to stimulate pathogenic infection. It was identified as Erwinia carotovora subsp. carotovora, which was a major pathogen, this study investigates the effect of fresh leaves powder of Eucaluptus and another one which was prepared before 10 months by using different concentrations of Eucaluptus leaves powder on total count number of isolated bacteria. Results showed that the leaves powder of Eucaluptus had inhibition activity on bacterial count. Inhibition value increased with increasing the level of plant extract. Best results were obtained at 2% which gave a complete inhibition after 48 hrs. Storage of leaves powder reduced the inhibition activity up to 42.9%. Rresults also showed that dusting potato tubers with plant leaves powder before storage for 8 weeks, reduced the infection percentage of stored potato tubers up to 15.5, 22.7, 25.2%. It reduced the weight–loss percentage to 18.4, 46.7, 54.2% when dusted with old plant leaves powder, with new plant leaves powder stored under ordinary conditions and with new powder stored under cold condition respectively. Therefore, pretreatment of potato tubers with Eucaluptus leaves powder as organic pesticides can prevent infection with soft rot disease